2019
DOI: 10.1017/s0140525x19000918
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in attacker-defender conflicts

Abstract: The distinction between attackers and defenders might help refine the understanding of the role of emotions in conflicts. Here, we briefly discuss differences between attackers and defenders in terms of appraisals, action tendencies, emotional preferences, and brain activities. Finally, we outline how attackers and defenders may differ in their response to emotion-based interventions that aim to promote conflict resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In other studies, loving-kindness meditation was shown to increase implicit and explicit measures of positive affect toward neutral strangers (Hutcherson, Seppala, & Gross, 2008) and to promote the enforcement of fairness-related norms in economic interactions (Weng et al, 2013). Extending this research to situations of interpersonal conflict, recent preliminary evidence from our laboratory showed that several weeks of regular compassion training, but not an active control training consisting of language learning, reduced schadenfreude toward a person with whom participants were in conflict (Cernadas Curotto, Sander, Halperin, & Klimecki, 2018).…”
Section: The Role Of Empathy and Compassion In Intergroup Relations Dmentioning
confidence: 83%
See 1 more Smart Citation
“…In other studies, loving-kindness meditation was shown to increase implicit and explicit measures of positive affect toward neutral strangers (Hutcherson, Seppala, & Gross, 2008) and to promote the enforcement of fairness-related norms in economic interactions (Weng et al, 2013). Extending this research to situations of interpersonal conflict, recent preliminary evidence from our laboratory showed that several weeks of regular compassion training, but not an active control training consisting of language learning, reduced schadenfreude toward a person with whom participants were in conflict (Cernadas Curotto, Sander, Halperin, & Klimecki, 2018).…”
Section: The Role Of Empathy and Compassion In Intergroup Relations Dmentioning
confidence: 83%
“…Pertaining to the question of generalizability, it seems that short-term loving-kindness or mindfulness interventions can reduce racial biases toward the population targeted in the training in intergroup situations (Lueke & Gibson, 2015; Stell & Farsides, 2016), while compassion training over several days can generalize to people who were not targeted in the training in both interpersonal (Cernadas Curotto et al, 2018) and intergroup contexts (Kang et al, 2014).…”
Section: Summary and Next Stepsmentioning
confidence: 99%